Covid-19; a threat to the Nigerian educational system: a way out - Anselm Ikenna Odo; Maigons Timothy Dodo; Tiri John Fidelis (Center for Humanities and Innovation Studies, 2020)
This paper posits that the outbreak of COVID-19 pandemic is a threat to the Nigerian educational system. The global lockdown of education institutions due to the Covid-19 outbreak is causing a significant interruption in students’ learning, disruptions in student performance assessments, and cancellation/postponement of exams. The researchers adopt the expository method in carrying out this work. The researchers conclude that effort should be made in educating citizens in an intercontinental world. This will make successful people in the coming decades to understand this interrelatedness and navigate boundaries to leverage their differences and work globally in a collaborative way.